Factors Related to the Implementation of Patient Safety - Anitha Anitha; Oktina Dwisusanti; Nuraidah Nuraidah; Kunti Wijiarti; Tiara Zakiyah Pratiwi; Siti Maemun (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patient safety is a critical global health issue. Despite solutions from JCI and WHO, 70% of medication errors still occur in many countries, including Indonesia. Objective: To identify factors influencing patient safety implementation by nurses at Sulianti Saroso Infectious Diseases Hospital (SSIDH). Methods: This cross-sectional observational study was conducted at SSIDH in October-November 2024. The population included 150 nurses, midwives, and heads of inpatient wards, selected using purposive sampling. Data were analysed using Kolmogorov-Smirnov, chi-square, and multiple logistic regression (p<0.05). Results: Most respondents were female and held a bachelor’s degree in nursing. Knowledge, attitude, and motivation were not significantly associated with patient safety implementation. Factors significantly influencing patient safety were age, duty room, and tenure (p<0.05). Nurses aged ≥40 years were four times less likely to implement patient safety standards compared to those <40 years (OR=4.04; 95%CI=1.68-9.72). Those working in non-intensive wards were 0.11 times less likely to implement standards (OR=0.11; 95%CI=0.05-0.27). Conclusion: Nurses/midwives should enhance patient safety implementation based on the six patient safety goals. Healthcare providers are encouraged to create programs to support quality improvement and reduce adverse events.